2011
DOI: 10.3390/s110807382
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Biodegradability of Treated Sewage Samples Using Synchronous Fluorescence Spectra

Abstract: Synchronous fluorescence spectra (SFS) and the first derivative spectra of the influent versus the effluent wastewater samples were compared and the use of fluorescence indices is suggested as a means to estimate the biodegradability of the effluent wastewater. Three distinct peaks were identified from the SFS of the effluent wastewater samples. Protein-like fluorescence (PLF) was reduced, whereas fulvic and/or humic-like fluorescence (HLF) were enhanced, suggesting that the two fluorescence characteristics ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 43 publications
3
20
0
Order By: Relevance
“…The BOD/COD ratio has been used as one of the well-adopted surrogates for biodegradability of TOC [10,11]. However, these measurements are time consuming, limiting their applications for rapid online monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…The BOD/COD ratio has been used as one of the well-adopted surrogates for biodegradability of TOC [10,11]. However, these measurements are time consuming, limiting their applications for rapid online monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…It is clearly observed that, from 900 to 1300 days (March 2004 and February 2005), this parameter increased to 4.3 and it remains almost constant on the monitoring stations from ST10 to ST15. Recall that this index can describe the organic matter biodegradability according to the following ranges [ 22 , 23 ]: If COD/BOD ≤ 2.5, then the organic matter is very degradable. If COD/BOD ∈ (2.5, 5), then the organic matter is moderately degradable.…”
Section: Resultsmentioning
confidence: 99%
“…This process differed for studied HAs as well as for analyzed fluorescent peaks, which was typical for the different origin, properties and components of HAs [7,12,18]. FI changes of decomposed EEM spectra in components 1 and 2 under example Zn doses are shown for PARAFAC and NMF algorithms in Figure 4 and Figure 5.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, fluorescence spectroscopy has been applied extensively to molecular characterization, differentiation and classification of humic substances as well as to monitor their changes in waste water or during processes of composting, mineralization or humification [3,11,12,13,14]. However, fluorescence detection can also be applied as an effective technique for understanding the mechanisms of intramolecular and intermolecular interactions between metals and humic acid [15,16].…”
Section: Introductionmentioning
confidence: 99%